Lived experiences of postpartum hypertensive women in Accra, Ghana - Kennedy Dodam Konlan; Hellen Akosua Asante; Cecilia Eliason (PLoS ONE, 2026)
Background Hypertension is a leading cause of adult mortality globally with postpartum hypertension posing distinct risk to women. In Ghana, particularly within the Accra Metropolis, there is a limited understanding of the lived experiences of women managing hypertension after childbirth. Aim We described the lived experiences of postpartum women diagnosed with hypertension receiving care in a resource-constrained setting in Accra, Ghana. Methods The study employed a qualitative, descriptive-phenomenological design. We purposively selected 16 postpartum women diagnosed with hypertension and receiving care. They were recruited from the postnatal clinic of the Greater Accra Regional Hospital. The data was collected via in-depth, semi-structured interviews using a pre-tested interview guide. The interviews were audio-taped and transcribed verbatim. We then conducted thematic analysis with the aid of NVivo 11.0. Results The analysis yielded three major themes; expectations about living with hypertension, self-efficacy in managing hypertension and environmental factors on the management of hypertension. On the expectation about living with hypertension, we identified the following sub-themes: optimism and hope for recovery as well as fear and uncertainty about complications. Regarding self-efficacy, the following sub-themes were identified: Confidence in adhering to treatment and challenges with lifestyle modification and monitoring. On the environmental factors influencing management of hypertension among the participants, we found the following sub-themes, spousal and family support, role of healthcare providers, social perceptions and stigma. Conclusion and recommendations Postpartum women diagnosed with hypertension face social stigma and have mixed feelings of hope, fear and uncertainty about developing complications. We recommend that midwives/nurses should design and implement targeted postpartum hypertension education programmes to promote confidence in the treatment, improve knowledge on the condition and enhance emotional resilience. Also, managers of antenatal and postnatal clinics must integrate spouses and faith-based organizations in the management of postpartum hypertension to reduce the associated social stigma.